2020
DOI: 10.4103/ijmr.ijmr_424_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of potassium titanyl phosphate laser & diode laser in the management of inferior turbinate hypertrophy: A randomized controlled trial

Abstract: Background & objectives: Inferior turbinate hypertrophy (ITH) is a common condition causing nasal obstruction. This study was undertaken to compare the efficacy of potassium titanyl phosphate (KTP) laser and diode laser in the reduction of the turbinate size. Methods: This randomized controlled trial included 209 patients with ITH. Pre-operative symptoms were assessed based on the Nasal Obstruction Symptom Evaluation (NOSE) score. Diagnostic nasal endoscopy was done to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Diode laser-assisted turbinate surgery is a popular procedure for improving nasal airflow. It is better absorbed by tissue than that of Nd: YAG lasers but with tissue ablation effects similar to a carbon dioxide laser [1]. Volk et al [4] evaluated diode laser-assisted nasal airflow and reported that rhinomanometry with decongestion has a predictive value for the enhancement of airflow after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diode laser-assisted turbinate surgery is a popular procedure for improving nasal airflow. It is better absorbed by tissue than that of Nd: YAG lasers but with tissue ablation effects similar to a carbon dioxide laser [1]. Volk et al [4] evaluated diode laser-assisted nasal airflow and reported that rhinomanometry with decongestion has a predictive value for the enhancement of airflow after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Diode-assisted laser turbinoplasty is a widely used surgical method for improving airflow as a treatment for nasal obstruction [1]. Predominantly caused by hypertrophy of the inferior nasal turbinates, nasal obstruction remains one of the most common conditions encountered in rhinology practice.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, both lasers altered the nose's mucociliary clearance for up to three months of postoperative follow-up. KTP laser was more productive than diode laser in improving the NOSE scores but with a slightly increased rate of complications in the early postoperative period [72].…”
Section: Potassium Titanyl Phosphate Laser (Ktp)mentioning
confidence: 92%
“…Another recent study compared the KTP laser with the diode laser [72]. This randomized controlled trial included 209 patients with ITH.…”
Section: Potassium Titanyl Phosphate Laser (Ktp)mentioning
confidence: 99%